The little rabbit - Dunn, Judy.; Dunn, Phoebe (New York : Random House, 1980)
Sarah's Easter gift rabbit becomes her constant companion and eventually gives birth to seven little bunnies.
AD570L
Decoding demand: 81 (very high) Semantic demand: 69 (high) Syntactic demand: 92 (very high) Structure demand: 81 (very high)
Accelerated Reader AR
edited hb 2015-06-16
Keywords: Rabbits; Fiction; Fiction